Patient-reported outcome measures: an on-line system empowering patient choice. (6th September 2013) - Wilson, J; Arshad, F; Nnamoko, N; Whiteman, A; Ring, J; Roy, B
Abstract: An innovative web-based system was developed to allow patient-reported outcome measures (PROMs) to be easily administered. Stakeholders guided the design and implementation. The software gives patients access to their current and previous scores. This pilot study focused on patients undergoing arthroscopic subacromial decompression, evaluated using the Oxford shoulder score (OSS). Patients showing good improvement in their OSS were offered the choice to return for routine follow-up clinic appointments, or continue rehabilitation, reassured by their improved score. Thirty-six of 117 patients were eligible. Thirty of these (83%) were opted to avoid further clinics. PROMs 2.0 can be used for any medical intervention with a validated PROM. Evolution and refinement is ongoing. Funding has been granted for 12 primary and secondary healthcare trusts to implement PROMs 2.0. Further work is needed to assess economic impact, patient views and satisfaction with the process.